PENGARUH ENGLISH SPEAKING ABILITY, HOSPITALITY, KONSEP BUDAYA DAN LOKASI HOTEL TERHADAP KEPUASAN TAMU DI SOLO PARAGON HOTEL - Melania Lulut Mariani; Heru Suwasono (STIE St. Pignatelli Surakarta, 2020)
The aim of this research is to learn the factors that are influencing the satisfaction of the guests who spend the days and spend the nights at Solo Paragon Hotel. Solo is one of the cities which has many visitors who spend their time for spending their holidays by enjoying culinary or having refreshing. Many people spend their time and the nights because they have to attend meetings or do their jobs. Satisfaction of the hotel guests is very important for the hotel management. It is considered as the achievement when the guests feel satisfied during their stay at that hotel. Satisfaction of the hotel guests is considered as the main key the hotel must provide as it will deterrmine the survival of the hotel. So, the hotel must always try to provide it. There are four factors that can influence the satisfaction of the hotel guests of Solo Paragon Hotel, they are : English Speaking ability, hospitality, the concept of culture and the location of the hotel. The guests get satisfaction during their stay and the nights they spend at Solo Paragon Hotel because of the complete facilities, the nice hospitality, good service and the strategic location of the hotel. The data are collected from the guests of Solo Paragon Hotel who spend the nights there by filling out the guest reiew and by having the interview. Then they are analyzed using qualitative and desctiptive methods. The result of the research showed that the English Speaking ability, hospitality, the concept of culture and the location of the hotel can influence the satisfaction of the guests of Solo Paragon Hotel.